Legal Approaches for Clinical Audits and Sanctions in Indonesian Health Service Facilities - Ida Ayu Sadnyini; David Christianto; I Gede Agus Kurniawan; Made Jayantara (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2024)
Laws and regulations in Indonesia have regulated health law to ensure that every person has the right to safe, high-quality, and affordable health services. Article 21 of Law No. 36 of 2009 on Health stipulates that every Health Service Facility must have a good and responsible health service management and governance system. However, the regulation of clinical audits as an effort to reduce the risk of negligence in healthcare facilities and how the process and sanctions for unintended errors in handling patients are still unclear. The research method used is empirical legal research. This research was conducted using the Legislative Approach, Conceptual Approach, and Case Approach. The results show that the regulation of clinical audits as an effort to reduce the risk of negligence in healthcare facilities is still unclear, so an approach based on the principles of justice, legal certainty, and usefulness is needed to reduce the risk of negligence in healthcare facilities. Furthermore, the process of audit and the imposition of sanctions for unintended errors in handling patients in healthcare facilities are subject to civil and criminal lawsuits. The conclusion of this study is that in clinical audits in Indonesia, an approach that prioritizes the principles of justice, legal certainty, and usefulness is needed to reduce the risk of negligence in healthcare facilities, so that all parties are treated equally, sanctions for errors must be fair and proportional, and preventive sanctions should focus on improving the qualifications of health workers, improving systems, and developing policies to improve health services and provide patients with the right to claim compensation and file complaints both civilly and criminally.